The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.7759/cureus.12518
|View full text |Cite
|
Sign up to set email alerts
|

Validity of TIMI Score for Predicting 14-Day Mortality of Non-ST Elevation Myocardial Infarction Patients

Abstract: Background Accurate management of non-ST elevation myocardial infarction (NSTEMI) patients can be achieved by stratifying risks as early as possible on hospital admission. Previously, the Thrombolysis in Myocardial Infarction (TIMI) risk score has been validated and used on patients presenting with NSTEMI or unstable angina (UA) in developed countries. The aim of this study was to assess the validity of the TIMI risk score in patients presenting with NSTEMI in Pakistan. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
(16 reference statements)
1
4
0
Order By: Relevance
“…In our study, the results approved that higher TIMI score was associated with higher incidence of in hospital complications and this is matched with the result obtained by [12] that revealed the TIMI risk score is a useful and simple score for the stratification of patients with high risk of 14-day mortality with reasonably acceptable discriminating ability in patients with NSTEMI-ACS. Therefore, its use among clinicians is suggested to apply strategic and precise interventions in monitoring these patients.…”
Section: Benhasupporting
confidence: 88%
“…In our study, the results approved that higher TIMI score was associated with higher incidence of in hospital complications and this is matched with the result obtained by [12] that revealed the TIMI risk score is a useful and simple score for the stratification of patients with high risk of 14-day mortality with reasonably acceptable discriminating ability in patients with NSTEMI-ACS. Therefore, its use among clinicians is suggested to apply strategic and precise interventions in monitoring these patients.…”
Section: Benhasupporting
confidence: 88%
“…Although it demonstrated an AUC of 0.80 for 30-day mortality prediction in Western populations [ 70 ], its applicability in Asian cohorts has been less convincing. Kumar et al (2021) found a TIMI score AUC of 0.78 in Pakistan [ 71 ], while a study in China found AUCs of 0.52, 0.50, and 0.52 for 6-month, 1-year, and 2-year mortality risks [ 72 ]. According to Indonesian research, the 14-day mortality prediction AUC for NSTEMI was 0.61 and 0.63 for UA [ 73 ], while Malaysian data revealed an in-hospital mortality prediction AUC of only 0.55 [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The TIMI risk score for NSTEMI/UA was developed to estimate the 14-day mortality risk and has remained unchanged for over two decades [5,24,62]. Although it demonstrated an AUC of 0.80 for 30-day mortality prediction in Western populations [70], its applicability in [71], while a study in China found AUCs of 0.52, 0.50, and 0.52 for 6-month, 1-year, and 2-year mortality risks [72]. According to Indonesian research, the 14-day mortality prediction AUC for NSTEMI was 0.61 and 0.63 for UA [73], while Malaysian data revealed an in-hospital mortality prediction AUC of only 0.55 [51].…”
Section: Plos Onementioning
confidence: 99%
“…Risk scores on the TIMI scale and Killip classification may serve as useful predictors of mortality after an AMI, with higher mortality risk associated with greater severity of congestive heart failure at presentation [ 18 , 19 ]. It is noteworthy that the type of intervention, specifically CABG, was identified as a significant predictor of lower mortality risk [ 20 ].…”
Section: Discussionmentioning
confidence: 99%